2019
DOI: 10.1016/j.socscimed.2019.112582
|View full text |Cite
|
Sign up to set email alerts
|

How do supply- and demand-side interventions influence equity in healthcare utilisation? Evidence from maternal healthcare in Senegal

Abstract: The launch of the Millennium Development Goals in 2000, followed by the Sustainable Development Goals in 2015, and the increasing focus on achieving universal health coverage has led to numerous interventions on both supply-and demand-sides of health systems in low-and middle-income countries. While tremendous progress has been achieved, inequities in access to healthcare persist, leading to calls for a closer examination of the equity implications of these interventions. This paper examines the equity implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Furthermore, during implementation, UHC policies should be closely monitored since they may have unexpected effects on equity. For instance, a recent study on maternal healthcare in Senegal shows that while a demand-side intervention (abolition of user fees) benefitted the poorer households more, thereby reducing inequity, a supply-side intervention (expansion of the availability of maternal health services) benefitted the richer households more, thereby increasing inequity [67].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, during implementation, UHC policies should be closely monitored since they may have unexpected effects on equity. For instance, a recent study on maternal healthcare in Senegal shows that while a demand-side intervention (abolition of user fees) benefitted the poorer households more, thereby reducing inequity, a supply-side intervention (expansion of the availability of maternal health services) benefitted the richer households more, thereby increasing inequity [67].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Bangladesh using DHS (Demographic and Health Survey) data in 2001 and 2010 presented an increasing percentage of antenatal care in urban (60% to 68%) and rural areas (37% to 49%). The research by Parmar and Banerjee 16 in Senegal and De La Torre et al 17 in Brazil and Colombia indicated that there was a gap in maternal health services utilization. A systematic review conducted by Çalışkan et al 18 confirmed that the earlier studies were dominated by the discussions of health services utilization; yet, they ignored the equity problems.…”
Section: Introductionmentioning
confidence: 97%
“…Another study in Senegal shows that a mere intervention on the supply side increased inequity between the rich and poor [25]. The grant aid in this study is a typical example of supply side intervention.…”
Section: Discussionmentioning
confidence: 58%